If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 3x = -12 Combine like terms: -5x + 3x = -2x -2x = -12 Solving -2x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-2'. x = 6 Simplifying x = 6
| 12=12b-4 | | 44=-7x-3(-x-4) | | -15+23=-2(x-8) | | -24=-8k-4k | | 6r^2+36=-33r | | a-4-2=-6 | | 2400+250x=6000 | | 4x-(x+2)= | | 232=40t | | 4G=20 | | 5=-7x+6x | | 5x-3(x-3)=-7+4x+10 | | 232=40*t | | y^4=16y | | 49x+11=6(7x+2)+7x-1 | | -9x-5y-6y= | | 4(n-3)=-15 | | (8-x)2=24 | | n-1-5=-10 | | 1+n+4n=16 | | y=5x^2+24x+27 | | 7x+4=7x+17 | | -4x+3(-x+14)=91 | | -20=-8p+6-2 | | -45=-10x-3 | | 5x+28=49-7x | | 3+4n=-5 | | 7+5m=3m-5 | | -4=7x-3x | | -1=99-10s | | 3t+13=-17+5t | | 7-5a-5+7b= |